Mitigating the Adverse Impact of Un-Deterministic Distributed Generation on a Distribution System Considering Voltage Profile - Aman, M. A.; Ahmad, S.; Noor, B.; Karam, F. W. (Engineering, Technology & Applied Science Research, 2018)
Electric power systems are enforced to operate near to their stability limit due to the fast increase in power demand. Therefore, voltage stability has become a primary concern. The main cause of voltage variations is the imbalance between generation and consumption. In order to mitigate variations in voltage profile, most of the modern electric power systems are adopting new emerging technologies such as distributed generation. Validation of standard voltage optimization is a difficult task when distributed generation is integrated to medium and low voltage networks. Integration of distributed generation (DG) will have diverse impacts on voltage levels when connected un-deterministically to the electric distribution system. This paper analyzes both the impacts of un-deterministic large and small size DG on voltage profile. Feasible solutions by incorporating reactors and increasing cross sectional area of cables, variation in voltage profile were mitigated. Detailed simulations were performed in ETAP by modeling and evaluating Kohat road grid station situated in Peshawar, Pakistan. The results anticipated that this approach can be useful to ensure standard voltage profile and better utilization of un-deterministic DG units.